THE EFFECT OF INTEGRATED EMERGENCY RESPONSE SYSTEM EDUCATIONAL VIDEOS ON EMERGENCY RESPONSE ATTITUDES OF STUDENTS AT SMA MUHAMMADIYAH 3 YOGYAKARTA - Marva Ahda Maritza; muhaji muhaji; Heri Puspito (Journal of Indonesian Anesthesiology Nursing, 2025)
Background: Emergencies can occur at any time and in any location, particularly in educational institutions characterized by high activity levels and susceptibility to emergency situations. The Integrated Emergency Response System (SPGDT) is designed to facilitate quick responses to emergency situations. The lack of appropriate attitudes in dealing with this situation is still a challenge for students.Methods: The methodology employed was quantitative, utilizing a one-group pretest-posttest design. The study sample comprised 69 grade X students from SMA (Senior High School) Muhammadiyah 3 Yogyakarta, selected by a simple random sampling method. Data was collected through questionnaires administered before and after the SPGDT educational video intervention. Results: The study's results demonstrate that video education can affect students' attitudes on emergency response with SPGDT among students at SMA Muhammadiyah 3 Yogyakarta, as evidenced by the Wilcoxon Signed Rank Test (Sig = 0.000).Conclusion: The SPGDT educational video has shown efficacy in enhancing students’ understanding and awareness for emergency situations.